Working conditions of subnational government workers in selected South and South-East Asian countries - Somjita Laha; Mayurakshi Dutta (International Labour Organization (ILO), 2024)
This study investigates the working conditions of subnational government (SNG) employees in select South and Southeast Asian countries, viz. Bangladesh, Nepal, Malaysia, Indonesia, and the Philippines. It is situated in the context of decentralized governance which transfers powers, responsibilities, and resources from central governments to subnational authorities for greater efficiency, accountability, and public service delivery. It also highlights the role of regional and local governments in Sustainable Development Goal (SDG) localization. The central research question is how decentralization and subsequent governance restructuring impact the quality, quantity, and inclusivity of SNG employment. Methodologically, the report is based on secondary sources in addition to in-depth qualitative interviews of representatives from trade unions, local authorities, SNG associations and international organizations. Secondary sources include data from government reports, national labour surveys, and international organizations and legal and policy documents on SNG operations and employment. The study shows that across all countries, there is a common challenge of balancing centralized authority with the autonomy and capability of SNGs. Human resource practices are not completely free of political interference in most countries. While recruitment and promotion are formalized and merit-based in theory, enforcement is inconsistent and politically influenced. Dismissal is regulated but can be arbitrary with varying extent of transparency. Among the SNG employees, there are significant disparities between the rights of permanent and contract workers and the latter has swelled in numbers with outsourcing as well as privatization of public services. Social security provisions for SNG workers are unevenly distributed. Collective bargaining rights and unionization are limited and practically non-existent for contract-based employment. There is a variety of restrictions on freedom of association and right to strike in most of the countries studied. Training and capacity-building programmes are available but primarily for permanent employees and not all workers in the SNG hierarchy. Policies for gender equity in SNG employment are present but not reflected, with fewer women in senior positions and mostly relegated to low-paying and less secure jobs. Overall, the study highlights the predominant trends of informalisation and privatization in SNGs and need for fiscal autonomy along with decent work conditions and inclusivity in public sector employment.
Keywords: 330